Exploring how social housing residents interact with building openings in a hot-humid climate - Solange Maria Leder; Andreia Cardoso de Oliveira; Celina Pinto Leão; Erivaldo Lopes de Souza (Elsevier, 2024)
In a hot-humid climate, natural ventilation is the most recommended strategy for obtaining thermal comfort indoors. The residents' behavior in opening windows and doors to promote natural ventilation is crucial for predicting thermal comfort, especially for low-income housing where energy costs can exceed household budgets. This study identifies residents' behavior in social housing in northeast Brazil (a hot-humid climate), focusing on actions to regulate thermal comfort with natural ventilation. The methodology comprehends field research, surveys, data processing, and analysis. Interviews with 375 individuals across two social housing complexes reveal the significant role of security and cultural factors in window control behavior. The results highlight the considerable role of security and cultural factors in shaping occupant behavior concerning window control. The residents indicated that they are stimulated to open the windows and doors right after they wake up and close them at bedtime or when leaving the house. Occupancy is a significant driving factor, but the sleep period (unconscious state) plays a crucial role in determining the closure of openings, even to housing units with a 2.0 m high wall on the plot land limits and security bars on windows. This study contributes to the understanding of the complex interplay between security, cultural factors, and thermal comfort regulation, proposing valuable insights for design and policy interventions aimed at improving living conditions in similar contexts.